Uma avaliação dos estudos de impactos ambientais (EIA) dos projetos de mineração da Região de Serra do Navio e Pedra Branca do Amaparí - AP - ARAÚJO, Keila Nazaré de Oliveira (2018)
Were used in this study, data from the technical advisory report (Technical Studies of Environmental Quality Water Resources in the region of Serra do Navio and Pedra Branca do Amapari-AP, Head of Projects Mining companies MPBA and MMX), held in the region sub-basin of the river Amaparí which includes the municipalities of Serra do Navio and Pedra Branca do Amaparí, ninety miles north of the city of Macapá (0 ° 30 'N and 1st 30' N and longitudes 51st 00 'W and 52 30' W ), extreme northern Brazil. The analysis was made from one set of information provided by the Public Prosecutor of Amapá on the Environmental Impact Assessment (EIA) projects related to mining in this field. The data for these ratings are not provided information related to the EIA implementation of the Project Amaparí Ore Gold Mining Amaparí of Pedra Branca Ltda (MPBA), with the analysis shown here are restricted to the analysis made material related to mining activities Iron. Previous studies conducted by the team responsible, show a strong tendency to minimize the impacts identified from the activities of companies operating in this area. The objective of this study was to evaluate the environmental impact studies and environmental impact report conducted in areas where mining companies carry out activities to identify possible irregularities of the same. With the implementation of this analysis it was found that there was a clear concern of the multidisciplinary team that performed the EIA to defend the proposed project by the entrepreneur in addition to the demonstration of lack of appropriate methods of environmental assessment.